KONSEP DASAR MANAJEMEN PENDIDIKAN ISLAM DAN PENERAPANNYA DALAM PENGEMBANGAN MADRASAH - Nazopah, Nada (eJurnal Al Musthafa, 2024)
This paper aims to find out the basic concepts of Islamic education management and its application in madrasah development. This paper is the result of a literature study by collecting data from various literature and information from available sources such as books, journals, reports and other documents. Madrasah development is a process that involves efforts to improve the quality, relevance and effectiveness of Islamic education institutions. Several important steps can be taken in madrasah development, including the preparation of Vision, Mission and Goals, self-evaluation, madrasah development planning, cooperation between stakeholders, and monitoring and evaluation. The implementation of madrasah development can be realized well when the madrasah is able to maximize aspects in the application of management functions, including through planning, good organization, implementation by maximizing finance, human resources, institutions and leadership and control by continuing to evaluate.